APPLICATION OF THE C5.0 ALGORITHM TO DETERMINE GOOD OR BAD ON 5S AUDIT RESULTS - Indra Aliyudin; Ari Purno Wahyu (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Darma Agung (LPPM_UDA), 2022)
Artificial Intelligence is currently growing and is widely used in various aspects of life in society. Likewise in today's corporate environment, we must be good at managing all activities so that AI can help in lightening and streamlining decision making at work. In terms of lightening this work, it is in the aspect of data management and data analysis. AI provides many methods and ways to analyze data so that the data can be used as a reference for employee self-assessment or even as a determinant of a company's business going forward. This study discusses the C5.0 algorithm which is implemented or tested against the 5S (Short, Set in Order, Shine, Standardize and Sustain) audit data set obtained from the company P.T. Bekaert Indonesia. This study uses two types of methods from the C5.0 algorithm model as a reference, namely the tree-based model and the rule-based model, besides that this study uses the cross fold validation method which is expected to increase the level of accuracy of the results of this study. This study was conducted aiming to find out whether the C5.0 algorithm can be implemented on the 5S audit result data set and has high accuracy or not. With the data collection method, analysis was carried out using RStudio software and the R programming language, this study shows that determining the good and bad 5S in an area can be done with the C5.0 algorithm with a tree-based model or a rule-based model and produces high accuracy.